The South China Sea in focus clarifying the limits of maritime dispute - Poling, Gregory B. (Center for Strategic & International Studies Rowman & Littlefield, 2013)
Satellite imagery and geospatial analysis tools offer an unprecedented opportunity to harness new technologies in order to help resolve boundary disputes. This report uses these tools to provide a first and necessary step toward tackling the overlapping maritime disputes in the South China Sea: determining which waters are and are not in dispute under international law. The report opens with a set of geographic information system (GIS)-based maps that provide an easily understandable benchmark against which policymakers and academics can judge the claims and actions of the South China Sea claimants. More detailed color maps and methodological information follow for those who want to dig deeper into the claims and the report's conclusions